2016
DOI: 10.1007/s12640-016-9649-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Treatment and Development of the Rat Cerebellum: Effects on the Neurogenetic Profiles and Settled Patterns of Purkinje Cells and Deep Cerebellar Nuclei Neurons

Abstract: The current paper analyzes the development of the male and female rat cerebellum exposed to hydroxyurea (HU) (300 or 600 mg/kg) as embryo and collected at postnatal day 90. Our study reveals that the administration of this drug compromises neither the cytoarchitecture of the cerebellar cortex nor deep nuclei (DCN). However, in comparison with the saline group, we observed that several cerebellar parameters were lower in the HU injected groups. These parameters included area of the cerebellum, cerebellar cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…(2) The cerebellum is highly vulnerable to insults, the expression of mutant genes and intoxication [43,44,45]. In this context, it has been reported that several spontaneous murine mutations, including lurcher, staggerer, reeler and weaver cause a marked reduction in the volume and shape of the cerebellum due to the severe depletion of neurons [46,47,48]. In addition, it has also been indicated that the selective elimination of neuron precursors with X-irradiation [36], platinum compounds [49,50], impairment of the thyroid status [51], ethanol [52] and virus infection [53] produce an important reduction in size of the cerebellar cortex.…”
Section: Justifying the Choice Of The Cerebellum As A Model To Assmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The cerebellum is highly vulnerable to insults, the expression of mutant genes and intoxication [43,44,45]. In this context, it has been reported that several spontaneous murine mutations, including lurcher, staggerer, reeler and weaver cause a marked reduction in the volume and shape of the cerebellum due to the severe depletion of neurons [46,47,48]. In addition, it has also been indicated that the selective elimination of neuron precursors with X-irradiation [36], platinum compounds [49,50], impairment of the thyroid status [51], ethanol [52] and virus infection [53] produce an important reduction in size of the cerebellar cortex.…”
Section: Justifying the Choice Of The Cerebellum As A Model To Assmentioning
confidence: 99%
“…Here, we show that a single administration of HU during embryonic life modifies the regular cytoarchitecture of the cerebellum and alters the neurogenetic profiles and settled patterns of PCs and DNC neurons. The results of this section are taken from a previous published paper [48].…”
Section: Embryonic Effects Of Hu Exposure: Long-survival Experimentsmentioning
confidence: 99%
“…(II) The cerebellum is highly vulnerable to insults, expression of mutant genes and intoxication [44][45][46]. In this context, it has been reported that several spontaneous murine mutations, including lurcher, staggerer, reeler and weaver cause a marked reduction in the volume and shape of the cerebellum due to the severe depletion of neurons [47][48][49]. In addition, it has also been indicated that the selective elimination of neuron precursors with X-irradiation [37], platinum compounds [50][51], impairment of the thyroid status [52], ethanol [53] and virus infection [54] produce an important reduction in size of the cerebellar cortex.…”
Section: Teratogenic Effects Of Hydroxyureamentioning
confidence: 99%
“…neurogenetic profiles and settled patterns of PCs and DNC neurons. The results of this section are taken from a previous published paper [49].…”
Section: Embryonic Effects Of Hu Exposure: Long-survival Experimentsmentioning
confidence: 99%
“…The major goal of this study is to analyze whether a single injection of BrdU, doses ranging from 25 to 300 μg/g b.w., alters the development of the cerebellar neuroepithelium. Dams were injected on embryonic day (E) 13, as it corresponds to the onset of Purkinje cells and deep cerebellar nuclei neurons neurogenesis in wild type rats (Altman & Bayer, 1997; Martí et al, 2015, 2016). The selection of the cerebellum was supported by the evidence that this region is highly vulnerable to poisoning (Samson & Claassen, 2017).…”
Section: Introductionmentioning
confidence: 99%